Preliminary Base Plate Selection - Stockwell, Jr. (Engineering Journal, 1975)
In supplement no. 3 to the AISC Specification, the allowable bearing stress of steel base plates on concrete was liberalized to agree with the latest design rules of the ACI Code. Based on these higher allowable bearing stresses, the author has developed design aids for rapid selection of base plates. Also, a new design procedure is proposed for lightly loaded column bases.